Strain-specifc predation of Bdellovibrio bacteriovorus on Pseudomonas aeruginosa with a higher range for cystic fbrosis than for bacteremia isolates - Saralegui, Claudia; Herencias, Cristina; Halperin, Ana; Caballero, Juan de Dios; Pérez Viso, Blanca; Salgado, Sergio; Lanza, Val F.; Cantón, Rafael; Baquero, Fernando; Prieto, M.Auxiliadora; del Campo Moreno, Rosa (My University, 2022)
This work aimed to evaluate the predatory activity of Bdellovibrio bacteriovorus 109J on clinical isolates of Pseudomonas aeruginosa selected from well-characterized collections of cystic fbrosis (CF) lung colonization (n= 30) and bloodstream infections (BSI) (n= 48) including strains selected by genetic lineage (frequent and rare sequence types), antibiotic resistance phenotype (susceptible and multidrug-resistant isolates), and colony phenotype (mucoid and non-mucoid isolates). The intraspecies predation range (I-PR) was defned as the proportion of susceptible strains within the entire collection. In contrast, the predation efciency (PE) is the ratio of viable prey cells remaining after predation compared to the initial inoculum. I-PR was signifcantly higher for CF (67%) than for BSI P. aeruginosa isolates (35%) probably related to an environmental origin of CF strains whereas invasive strains are more adapted to humans. I-PR correlation with bacterial features such as mucoid morphotype, genetic background, or antibiotic susceptibility profle was not detected. To test the possibility of increasing I-PR of BSI isolates, a polyhydroxyalkanoate depolymerase defcient B. bacteriovorus bd2637 mutant was used. Global median I-PR and PE values remained constant for both predators, but 31.2% of 109J-resistant isolates were susceptible to the mutant, and 22.9% of 109J-susceptible isolates showed resistance to predation by the mutant, pointing to a predator¿ prey specifcity process. The potential use of predators in the clinical setting should be based on the determination of the I-PR for each species, and the PE of each particular target strain.